Exploring the gaps between training and expected job skills of public health graduates to identify a way forward - Habib Ur Rehman; Mehjabeen Musharraf; Shiraz Shaikh (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the non-alignment between what is taught in academic programmes for public health and what is actually needed or expected in the field. Method: The qualitative phenomenological study was conducted from October 2020 to April 2021 in Karachi after approval from the institutional ethics review board of Jinnah Sindh Medical University, Karachi. The sample comprised major stakeholders including representatives of public health institutions and organisations involved in the implementation of public health programmes. Data was collected through in-depth interviews and focus group discussions using a guide after content validation by an expert. Data was analysed using both inductive and deductive approaches. Results: A total of 13 in-depth interviews and 5 focus group discussions were conducted. Regarding gaps in the process of curriculum development, 2 major concerns emerged; lack of comprehensive involvement of experts in different fields of public health in designing the curriculum, and the lack of incorporation of the feedback provided by students in revising the curriculum. Regarding the content of curriculum, three main themes emerged; theoretical nature of courses, lack of uniformity in all programmes, and poor local contextualisation. The casual approach of students and barriers faced by them in joining public health programmes also affected the quality of such programmes. Conclusion: Three broad areas of improvement were identified, which included improvement in curriculum, methods of learning, and improving students’ approach. Key Words: Public health education for professionals, Public health practice, Public health schools.